The effectiveness of instagram social media as an online promotion strategy @kraton_solo among communication science students at ums - Fitriyanto, Bima Akbar; Santoso, Budi (Jurnal Mantik, 2024)
The role of technology plays a crucial part in increasing the popularity of tourist destinations today. Social media is highly diverse and offers many benefits to its users, especially in terms of finding places to visit. This research aims to determine the extent of the influence of social media (Instagram) in online promotion @kraton_solo. This study uses a descriptive quantitative research type with a survey method, which emphasizes explaining the influence of the AIDA method (Attention, Interest, Desire, Action). The data collection technique in this research is using primary data. The sampling technique used is nonprobability sampling. The population in this study consists of @kraton_solo followers and Communication Science students (UMS) who follow the @kraton_solo account, totaling 25,500 followers. Descriptive Statistical Analysis Based on the table above, it can be seen that the average value of Attention is 19.19. Interest is 18.31. Desire is 10.07. The average value of Action is 09.77. The average value of Visiting Decision is 10.46 4.3 Research Results (Hypothesis Testing) Based on table 4.3 above, the calculation of multiple linear regression using the SPSS program version 21.0 for windows. The results obtained are F calculated at 40.108 and a probability of 0.000. Because sig 0.000 < 0.05, it can be concluded that the variables of attention, interest, desire, and action together influence the decision to visit